Penerapan Model Student Team Achievement Division untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa Kelas XI MIA I pada Konsep Sistem Gerak pada Manusia - Amalia, Nurul (Biocaster : Jurnal Kajian Biologi, 2023)
This study aims to increase the activity and learning achievement of class XI MIA I SMA Negeri 5 Balikpapan in the academic year 2021/2022. The subjects of this study were students of class XI MIA I SMA Negeri 5 Balikpapan for the 2021/2022 academic year. This research is a classroom action research (CAR) using two cycles. The instruments used in this study were observation sheets of student learning activities and student achievement test sheets. The results showed that the results of student learning activities in the first cycle reached 72.14% in the good category, while in the second cycle it reached 86.43% in the very good category. The classical completeness of student achievement in the first cycle is 50%, while the classical completeness in the second cycle is 60%. Thus, it can be concluded that the application of the Student Team Achievement Division (STAD) can increase student activity and achievement in class XI MIA I SMA Negeri 5 Balikpapan in the 2021/2022 academic year.